Analisis Kelembagaan Dinas Pemberdayaan Perempuan Perlindungan Anak dan Keluarga Berencana dalam Penanganan Stunting - Ella Putri Angelina; Esa Septian; Rupiarseh Rupiarseh (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
Stunting is a health problem that needs to be avoided because it greatly affects an individual's survival. This disease often appears in Indonesia today and inhibits growth. Stunting has the potential to be very bad for sufferers, so prevention needs to be carried out by several institutions. Institutions related to this problem include health institutions, DP3AKB, and other institutions. Analyzing institutions is assessing or observing and describing an object. This time we will observe the DP3AKB institution in Bojonegoro Regency in reducing stunting rates. In analyzing institutions, researchers use institutional theory according to J. William, which has five variables, namely: leadership, doctrine, programs, resources, structures or processes. In handling stunting, DP3AKB plays a role in education or outreach. This institution works well so that goals can be achieved which can reduce stunting. The aim of this research is to determine the function or role of DP3AKB in helping reduce stunting, especially in Bojonegoro Regency.